HUBUNGAN PERSEPSI DENGAN PERANAN SISWA DALAM PELAKSANAAN PROGRAM KEGIATAN PUSAT INFORMASI KONSELING KESEHATAN REPRODUKSI REMAJA DI SMP N 2 PARIAMAN - Desyolmita, Nunung; ., Firman (Konselor, 2013)
Program Information Center Counseling Adolescent Reproductive Health is an activity to alleviate the problems of students in the school. The reality on ground activities are less likely to get a positive response from students. This study aims to reveal students' perceptions and their relation to the role of students in the program implementation activities PIK-KRR. Correlational descriptive research with a population of 496 students, 84 students sampled, using proportional random sampling technique. Results showed students 'perceptions enough, the role of the students enough and significant relationship between students' perceptions of the role of students in the implementation of program activities PIK-KRR. Keyword: students' perceptions ; the role of student.